A Need Assessment of Communication and Employee Performance: A Case Study of PKK Auto Partnership Limited, Thailand - Phachirananwanich, Thanthicha; Fernando, Maria Socorro C L (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
Both company communication and employee performance play an increasingly essential role in many organizations throughout the world. Many companies are struggling to enhance better company communication and employee performance through training and career development because these can lead to the good image of organization and the effectiveness of entire organizational performance. This research intended to discover the priority needs for the improvement in terms of the forms of communication, company communication, and employee performance by using the case study of PKK Auto Partnership Limited in Thailand. There are two major research objectives including 1) To determine the current situation and expected situation of the company’s communication and employee performance based on perceptions of employees and customers and 2) To design a training plan based on the results of the research study. To prioritize the needs for enhancing better company communication and employee performance, the quantitative research method using Priority Needs Assessment Modified (PNIModified) was utilized in this research study. The key results based on the quantitative findings were the company communication (PNIModified = 0.1644) sorted as the 1st rank of priority needs index followed by forms of communication (PNIModified = 0.1588) and employee performance (PNIModified = 0.1468), respectively. A training plan was designed based on the results of the study.